The Formulation and Evaluation of Lipstick with Brazilline Pigment of Caesalpinia sappan L - Yuniarti Falya (Unit Penelitian dan Pengabdian Kepada Masyarakat (UPPM) STIKES Dirgahayu Samarinda, 2022)
Lipstick is one of the decorative cosmetics used to beautify the lips with attractive colors. A good lipstick preparation must be easy to apply, not irritating, not sticky, and can maintain the durability of the color that sticks to the lips. Secang wood contains pigments, tannins, brazilin, tannic acid, resin, resorcin, brazielin, sappanin, and gallic acid. This study aims to make a formulation of sappan wood lipstick (Caesalpinia sappan L.) as a colorant when applied with a concentration of 10%, 14%, 18% and 22% of the lipstick extract of sappan wood (Caesalpinia sappan L.) formula which produces color in the formulation. physically and chemically stable lipstick preparations. The preparation was carried out by maceration using 96% ethanol solvent for 3 x 24 hours and evaporated to obtain a thick extract of secang wood. Lipstick testing was carried out physically and chemically including organoleptic test, spreadability, melting point, preference test, irritation test and pH test. The results show different colors in the four formulas, the best formula is Formula II with a concentration of 14% seen from several favorite tests 73.33%, irritation test shows negative results, spreadability shows good results, melting point at 72°C, pH 5.9, and not irritating.